2021
DOI: 10.1111/psyg.12792
|View full text |Cite
|
Sign up to set email alerts
|

Suvorexant with or without ramelteon to prevent delirium: a systematic review and meta‐analysis

Abstract: Delirium is a common and serious neurobehavioral syndrome, associated with prolonged hospital stays, and increased morbidity and mortality. As it remains unclear whether suvorexant with or without ramelteon prevents delirium in elderly hospitalized patients, we conducted a systematic review and meta‐analysis to evaluate, searching the PubMed, Cochrane Library, Web of Science, EMBASE, and EBSCOhost databases for all randomized controlled trials (RCTs), case–control studies, and cohort studies that investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…In this retrospective cohort study, we investigated the association among sleep-inducing drugs and the prevention of delirium in patients hospitalized in general medical-surgical settings for nonpsychiatric conditions. Although previous meta-analyses showed that suvorexant was effective in preventing delirium, 35 the present cohort study is the first to include two orexin receptor antagonists (suvorexant and lemborexant) and a melatonergic agonist (ramelteon) and examine their association with delirium prevention. Moreover, while previous studies [26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]43,44 on delirium were conducted in specific population groups at a high risk of delirium, such as older adults, ICU patients, and those in postoperative periods, this study included the general population; therefore, it may be valuable in that it reflects a wider range of cases observed in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this retrospective cohort study, we investigated the association among sleep-inducing drugs and the prevention of delirium in patients hospitalized in general medical-surgical settings for nonpsychiatric conditions. Although previous meta-analyses showed that suvorexant was effective in preventing delirium, 35 the present cohort study is the first to include two orexin receptor antagonists (suvorexant and lemborexant) and a melatonergic agonist (ramelteon) and examine their association with delirium prevention. Moreover, while previous studies [26][27][28][29][30][31][32][33][34][36][37][38][39][40][41]43,44 on delirium were conducted in specific population groups at a high risk of delirium, such as older adults, ICU patients, and those in postoperative periods, this study included the general population; therefore, it may be valuable in that it reflects a wider range of cases observed in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Suvorexant has been reported to be effective in preventing delirium in randomized controlled trials (RCTs) in older adults, 30,31 retrospective studies in ICU patients, 32,33 retrospective studies on patients who have undergone postcoronary artery bypass surgery, 34 and a systematic review and meta-analysis. 35 Moreover, ramelteon has been reported to be effective in preventing delirium in older adults, 36,37 ICU patients, 38 and patients who have undergone hepatectomy according to a retrospective study. 39 However, meta-analyses have reported that ramelteon exhibits a limited effect on preventing delirium, 40,41 and no consistent findings have been obtained regarding its effectiveness in preventing delirium.…”
mentioning
confidence: 99%
“…W literaturze pojawiają się doniesienia o skuteczności w zapobieganiu delirium nowych leków nasennych -suworeksantu (antagonista receptora dla oreksyn) oraz ramelteonu (agonista receptorów dla melatoniny). Z uwagi na ograniczone dane leki te wymagają dalszych badań [50]. Lekiem o innym mechanizmie badanym w tym wskazaniu jest masupirdyna -antagonista receptora 5-HT6 [51].…”
Section: Inneunclassified
“…Delirium prevention using suvorexant is a field of interest, since the sleepwake disturbance has been regarded as one of the important risk factors for delirium [4]. To date, two small randomized controlled trials and nine observational studies have been published, and two systematic reviews and meta-analyses summarized the data [5][6][7][8][9][10][11][12][13][14][15][16][17]. The metaanalysis by Tian et al included 2,594 participants in total and the effects on delirium were an odds ratio (OR) of 0.25 with a 95% confidence interval (CI) of 0.07 to 0.95 for two randomized controlled trials and an OR of 0.36 with the 95% CI of 0.23 to 0.56 for nine observational studies [17].…”
Section: Introductionmentioning
confidence: 99%